Corrosion behaviour investigation of 460 low alloy steels exposed in the natural deep-sea environment. (18th August 2019) - Duan, Tigang; Xu, Likun; Ding, Kangkang; Peng, Wenshan; Hou, Jian; Guo, Weimin; Cheng, Wenhua
ABSTRACT: The corrosion behaviours of 460 low alloy steels were investigated by the field exposure corrosion experiments with various long periods and 1200–3000 m depths in the natural deep-sea environment. XRD analysis results indicate that corrosion products of β-FeOOH, γ-FeOOH and Fe3 O4 increase and the corrosion product of α-FeOOH decreases with the exposure sea depth extending. Electrochemical experiment results reveal the corrosion status is aggravated with the exposure sea depth extending: corrosion potentials shift negatively to a minimum self-corrosion potential of −0.590 V (vs. SCE) and charge transfer resistances decrease to a minimum of 278 Ω cm 2 . Corrosion behaviours analysis shows that the average corrosion rate decreases with the time increasing and reaches a maximum value of 101 μm a −1 . The maximum pitting depth varies between 63.0 μm and 138 μm. Gray relational analysis shows that the corrosion rate of 460 steel is most influenced by the pressure and dissolved oxygen concentration of deep sea, exhibiting a positive correlation relationship.